Effectiveness of a novel long-lasting pyriproxyfen larvicide (SumiLarv®2MR) against Aedes mosquitoes in schools in Yangon, Myanmar - Oo, Sai Zaw Min; Thaung, Sein; Maung, Yan Naung Maung; Aye, Khin Myo; Aung, Zar Zar; Thu, Hlaing Myat; Thant, Kyaw Zin; Minakawa, Noboru (Parasites & vectors, 2018)
Background Mosquito-borne diseases are prevalent in Myanmar, with the number of dengue cases showing a significant increase in recent years. Dengue vectors have developed resistance to insecticides and currently used larvicides show only short-term effectiveness. As a result, an alternative larvicide is urgently needed. The present study evaluated the larvicidal effectiveness of long-lasting pyriproxyfen resin discs (SumiLarv®2MR) against dengue virus vectors in schools in Hlaing Thar Yar Township, Yangon. Results The proportion of Aedes mosquito-infested containers was significantly reduced in the schools applied with the larvicide (OR: 0.24, 95% CI: 0.12–0.48) while there was little reduction noted in the control schools (OR: 0.97, 95% CI: 0.55–1.72). The density of infested containers was also significantly reduced in the intervention schools (Beta: -1.50, 95% CI: -1.98– -1.04), but there was no significant reduction in density in the control schools (Beta: -0.19, 95% CI: -0.53–0.14). The proportion of adult emergence was less than 20% in the treated water collected from the intervention schools for six months, while the proportion was over 90% in the untreated water. In addition, eight-month-old SumiLarv®2MR resin discs were still 100% effective when tested in the laboratory. More than 50% of the discs disappeared from treated containers within two months of intervention. Conclusions SumiLarv®2MR was effective in reducing Aedes -infested containers at least six months after its application in schools. This new pyriproxyfen formulation has great potential for improving the current dengue vector control program in Myanmar.